Morphology‐Dependent Bioadhesion and Bioelimination of Hyaluronan Particles Administered in the Bladder. Issue 5 (18th February 2022) - Diaz-Salmeron, Raul; Toussaint, Balthazar; Cailleau, Catherine; Ponchel, Gilles; Bouchemal, Kawthar
Abstract : Intravesical instillation allows for direct exposure of the urothelium to a drug. However, the therapeutic efficacy is often limited by the rapid elimination of the drug from the bladder. In this investigation, it is hypothesized that the morphology of nanoparticulate drug delivery systems could significantly impact bioadhesion and bioelimination from the bladder. Bioadhesion kinetics evaluated ex vivo on rat bladder mucosa demonstrates that particles with a flattened morphology, denoted as nanoplatelets, are rapidly attached to the mucosa at a lower concentration than nanospheres. The two particles have comparable surface potentials and equivalent volumes and are composed of hyaluronan, a nonsulfated polysaccharide that plays a significant role in restoring the bladder glycosaminoglycan layer. The bioaccumulation and bioelimination studied in vivo reveal that the nanoplatelets are eliminated from the rat bladders less rapidly than nanospheres. This investigation suggests that the bioadhesion of HA could be improved by optimizing particle morphology, opening new opportunities for the treatment of local urothelial diseases, such as interstitial cystitis/painful bladder syndrome, by restoring the loss of the glycosaminoglycan layer. Abstract : Intravesical instillation is limited by rapid drug elimination. Herein, it is demonstrated that the flat morphology of hyaluronan particles significantly improves bioadhesion and decreases bioelimination from the bladder. Bioadhesion kinetics are evaluated ex vivo on rat bladder mucosa, while particle bioelimination was studied in vivo using a real‐time imager system. This investigation could open opportunities for efficient drug delivery.